The effect of the aqueous and methanol fennel stem extracts (Foeniculum vulgare Miller) on isolated rat ileum contractility - Gočmanac-Ignjatović, Marija; Kitić, Dušanka; Radenković, Mirjana; Kostić, Milica; Milutinović, Milica; Nedin-Ranković, Gorana; Branković, Suzana (Vojnosanitetski pregled, 2020)
Background/Aim. The fennel (Foeniculum vulgare Miller, Apiaceae) has a long history of use as traditional herb medicine due to its carminative properties. The study was aimed to investigate the effects of aqueous and methanol fennel stem extracts on intestinal activity. Methods. Relaxant activity of aqueous and methanol fennel stem extracts was evaluated in vitro in three experimental models: spontaneous contraction, acetylcholine and potassium chloride (KCl)-induced contraction of an isolated rat ileum. The composition of aqueous and methanol fennel stem extracts was qualitatively analyzed using the high performance liquid chromatographic (HPLC) analysis. Results. In the presence of an aqueous fennel stem extract at a concentration of 3 mg/mL, the inhibition of the spontaneous contractions of isolated rat ileum was 35.05% ± 3.57%. In presence of a methanol fennel stem extract at the same concentration, the maximum reduction of the spontaneous contractions was 48.91% ± 6.31%. The extracts in a concentration-dependent manner significantly inhibited the acetylcholine and KCl induced contractions of the isolated rat ileum (p
Keywords: ileum; rats; foeniculum; acetylcholine; potassium chloride; treatment outcome.